Монгол Улсын Эдийн засгийн хөгжлийн дэд сайд О.Чулуунбатын хэлсэн үг (Journal of International Studies, 2014)
English title: Opening remarks by H.E. Mr. O.Chuluunbat, Vice Minister for Economic Development of Mongolia